On mapping onto self-organized criticality - Wiśniewski, Andrzej (Studia Informatica. System and information technology, 2006)
In the report we have discussed a few aspects of SOC concept which in general have strongly influence on explicitness of mapping process. SOC idea is based on group of models and/does not seem to give quite clear instructions whether mapped phenomena exhibit SOC or not. To present the problem we have performed a computer simulation in order to investigate the effect of the critical point within the system evolution process without conservation. We have considered that on two-dimensional cellular automata whose rule consists of one or two subrules. The first one, based on Conway’s model (or very similar to), has represented the local behavior of transmission processes and has been applied in the experiment synchronously, as a fundamental mode. The second one, called a transport rule, has been applied sequentially. That subrule has described the motion of a fraction of individuals. As a result of comparing models of the various sets of rules for the applied size of lattice, we could find that the modified Conway’s model would be merely treated as subcritical.